Pelatihan Teknik Closing dengan Digital Marketing Bagi Pelaku UMKM - Didin Herlinudinkhaji; Lingga Kurnia Ramadhani; Nindita Erwanti; Yunila Putri Dwi Ariyanti; Condro Pargianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of the digital world has a big impact on business people including small businesses at the Micro, Small and Medium Enterprises (MSMEs) level, this makes the ways and methods of doing business for MSMEs change, be it from offers, sales, promotions, services to the closing stage of sales (closing). For this reason, the purpose of this community service is to provide knowledge to MSME actors techniques or ways to make buyers quickly decide to make a purchase or close a sale called a closing technique using digital marketing. The method used in the implementation of this activity is a lecture and direct practice of implementing digital marketing for closing sales. The stages of implementing this community service activity include opening, introduction to digital marketing, product analysis with google trends, social media analysis for business, marketing strategies, closing techniques and creating business accounts